PEMAKNAAN AYAT AL-QURAN DALAM MUJAHADAH: Studi Living Qur’andi PP Al-Munawwir Krapyak Komplek Al-Kandiyas - Moh. Muhtador (Jurnal Penelitian, 2014)
DEFINITION OF THE VERSES OF THE QUR’AN IN MUJAHADAH (THE STUDY OF THE LIVING QUR’AN IN PP Al-MUNAWWIR KRAPYAK Al-KANDIYAS COMPLEX). The Qur’an as a guideline of life for Muslims and became the authoritative source in the realm of social reality has developed its meaning. Relation to the development of meaning in al-Qur’an is the potential of the Qur’an itself that keeps studied and preserved in the realm of the theoretical and praxis. In the theoretical realm of the Qur’an continues to experience the reconstruction of understanding, reconstruction is related to the Qur’an itself, as is the case. About what enclosing the Qur’an when down and what is contained in the Qur’an itself. Both of them does not close the possibility to continue to be developed with different variants of the science to be an approach in digging the content of its science value, such as sociology, anthropology, historiy, and hermeneutic. On the other hand the study of praxis, in relation to the Qur’an is how the verses of the Qur’an are understood and practiced. This study assesses the reality of the society with the Qur’an. In that sense, the strive of mujahadah devotee community when interacting with verses of the Qur’an which become the practices and had a magical and mystical power. Because in practice a conviction verses are read when mujahadah contains a value that cannot be expressed. So the verses of the Qur’an become alive amongst the people, but it’s merely as a discourse and perception, it also confines the substantial meaning of a verse which contained in it when being interpretated or takwil.